Effect of unsaponifiable fraction of seeds of Hygrophila spinosa T. Ander on testosterone production of rat Leydig cells in vitro - Vyas, Niraj; MANAN RAVAL, (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective of the study: Seeds of Hygrophila spinosa (HS) T. Ander (Acanthaceae) are traditionally used as aphrodisiac and spermatogenic in Indian System of medicine. Preliminary phytochemical screening of plant revealed the presence of triterpenoids and sterols in seeds. The study was planned to assess the effect of unsaponifiable fraction prepared from seeds of HS on isolated rat Leydig cells for testosterone (T) production using in vitro method. Materials and methods: Leydig cells were isolated from wistar rats, aseptically, in vitro by collagenase cell dispersion method. Cells (2 X 106 cells/ml) were then incubated with unsaponifiable fraction of HS (10, 100 and 1000 Âµg/ml dose levels in triplicate) in incubator at 37Â°C under atmosphere of 95% CO2 condition for 3 hours in aseptic condition. Dehydroepiandrosterone (DHEA) was used as positive control in the study. The amount of T secreted in culture media was estimated using HPTLC. Benzene: Ethyl acetate (5:5% v/v) was employed as mobile phase and silica gel G F254 aluminum coated TLC plate as stationary phase. Results: The results indicated dose dependent increase in testosterone concentration in test groups. Isolated rat Leydig cells treated with the test fraction showed increased amount of testosterone present in culture media as compared to that of control. Conclusion: Unsaponifiable fraction prepared from seeds of HS showed ability to enhance biosynthesis of T in Isolated rat leydig cells. In vitro studies showed that the fraction might act locally in testis on Leydig cells and stimulated testosterone synthesis.